CORRELATION OF CRIMINOGENIC AND CORRUPTION FACTORS IN THE SCIENTIFIC EXPERTISE OF DRAFTS OF NORMATIVE LEGAL ACTS - G. B. Kyssykova (Russian Journal of Economics and Law)
The article is devoted to the methodological recommendations for carrying out the scientific expertise of drafts of normative legal acts, in particular, their basic constituent elements, which can help to reveal the drawbacks in the researched draft of a legal act, that is, the criminogenic and corruption factors.